Pembuatan Flashcard Audio Visual untuk Peningkatan Pemahaman Sex Education Anak Usia Dini - Sutriyani, Wulan; Wiranti, Dwiana Asih; Muhaimin, Muh; Wulandari, Elma Tiara; Ningsih, Rahma Dwi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Sex education is important in the world of education because of the rise in cases of sexual harassment due to the lack of understanding of sex education from an early age. The partner school, namely KB Mentari Kudus, has a problem with the behavior of early childhood jokes that lead to pornographic words as well as verbal bullying and actions. In addition, teachers also have not presented digital learning media in the learning process. The mentoring activity for making audio visual based flashcard media as a solution offered to partners has the aim of increasing students' understanding of sex education. Teachers are expected to be able to increase creativity in providing learning media, especially related to sex education. The method used in this service includes 5 stages namely socialization, training, application of technology, mentoring, and sustainability. Community service activities get the result that partners feel able to develop competence in making innovative learning media for early childhood. Sex education is important to be taught to early childhood where 93.75% of partners strongly agree with this statement. Media needs are also approved by partners with 81.25% and are also supported by the importance of innovation in learning. Partners are also very helpful in making audio visual based flashcard media. The implementation carried out by partners and the service team obtained 93.75% results audio visual flashcard media is suitable for sex education material for early childhood.